Mowing increases fine root production and root turnover in an artificially restored Songnen grassland - Luo, Yan; Wang, Xinyu; Cui, Meng; Wang, Jing; Gao, Yingzhi (Plant and soil, 2021)
Aims Mowing is a common management practice in grassland ecosystems. However, how mowing affects fine root dynamics remains poorly explored. Methods A field experiment was conducted to study how mowing influences root dynamics in artificial and natural grasslands for three consecutive years with root-window method. Results Root production among the treatments varied from 312 to 681 m m −2 each year and fine root turnover varied between 1.58 and 3.41 times per year. Fine root production, root mortality and root standing crop exhibited clear seasonal patterns in both the natural and artificial grasslands, and these were mainly driven by precipitation and temperature. Root production and root turnover responded differently to mowing in different types of grassland. In the artificially restored grassland, mowing significantly increased root production and root turnover (15.01% and 13.06%, respectively) and decreased the root lifespan by 14.60%. In contrast, none these effects were significant in the naturally restored grassland. The mowing-induced increase in root production and root turnover in the artificially restored grassland was mainly due to an enhancement in aboveground biomass and soil moisture. However, the lack of an effect on these parameters from mowing in the naturally restored grassland may be due to the higher species diversity. Conclusions Our findings demonstrate that mowing might accelerate root turnover and improve belowground productivity in the artificially restored grassland, highlighting that suitable mowing is an efficient way to manage artificial grasslands from the perspective of the dynamics of root system.